THE ROLE OF CORPORATE GOVERNANCE IN THE CAPITAL STRUCTURE OF BANKING COMPANIES - Natsir, Khairina; Bangun, Nurainun (Graduate Program of Universitas Tarumanagara, 2025)
Decisions regarding capital structure are an important decision taken by financial managers to remain competitive in the long term. A strong capital structure is very important for banks, because with a strong capital structure banks can face global competition and economic crises that can occur at uncertain times. Banks can have a strong or optimal capital structure if the existing capital can be used well. Therefore, good corporate governance is needed so that existing capital can be used or managed well to achieve banking goals and make the right decisions in facing competition and the economic crisis. This research was conducted with the aim of determining the influence of corporate governance on the capital structure of banking companies. Corporate governance is measured by looking at the size of the board of directors, the size of the board of commissioners and managerial ownership, while capital structure is measured by the debt-to-equity ratio. The sampling method used the purposive technique for 37 banking sector companies listed on the Indonesia Stock Exchange in 2018-2022. The secondary data obtained from annual reports of banking companies. This research uses robust regression analysis. The research results show that the size of the board of directors has a positive and significant influence, the size of the board of commissioners has a positive and significant influence on the capital structure, and managerial ownership has a negative and significant influence on the capital structure of banking companies listed on the Indonesia Stock Exchange.